Rapid and simple detection of Listeria monocytogenes using real closed dumbbell-mediated isothermal amplification - Zhang, Yanli; Wu, Xinyao; Zhong, Yeling; Chen, Xuhan; Guo, Fei; Ouyang, Guifang; Mao, Rui (Frontiers in Microbiology, 2025)
IntroductionListeria monocytogenes (L. monocytogenes) is a well-known widespread food-borne pathogen that poses a threat to public health. Suitable detection methods are needed to effectively control and prevent pathogenic L. monocytogenes infections.MethodsThis study aimed to develop a novel closed dumbbell-mediated isothermal amplification (CDA)-based assay to achieve rapid and simple detection of L. monocytogenes. The newly developed CDA technology is capable of amplifying DNA targets with high sensitivity and specificity. The conserved hly gene of L. monocytogenes was taken as a target for the establishment of the CDA method. All primers were selected and evaluated by real-time fluorescence monitoring, and endpoint visual judgement was indicated by hydroxy naphthol blue (HNB).ResultsThe specificity and sensitivity of this CDA-based diagnostic system were determined after the evaluation of 560 batches of DNA samples. The detection limit of the L. monocytogenes O-CDA assay was 1 copy/μl using artificial samples. The results of real-time fluorescence-based O-CDA coupled with melting curves analysis showed that the method would achieve rapid and accurate diagnosis of L. monocytogenes, and can be employed as an alternative to qPCR in diagnostic practice. Moreover, the L. monocytogenes O-CDA method monitored by real-time fluorescence and endpoint hydroxy naphthol blue (HNB) based colorimetric assay displayed the same sensitivity, specificity, and accuracy, which would be helpful to realize onsite pathogen surveillance.DiscussionThe real-time fluorescence plots and following melting curve analysis-based L. monocytogenes O-CDA were suitable for laboratory-based diagnosis. Considering the portable manipulation of the HNB-based colorimetric detection system, our results shed light on its potential application for on-site L. monocytogenes surveillance. The developed CDA-based methods are rapid, simple, reliable, and sensitive in several samples, showing potential to manage the task of L. monocytogenes monitoring more easily.